Literasi dalam pendidikan : perubahan dan cabaran - Pandian, Ambigapathy (Kuala Lumpur : Pusat Pembangunan dan Pendidikan Komuniti, 1999)
Literacy and education in Malaysia; papers of a conference.
Includes bibliographical references.
In Malay.
Keywords: Literacy -- Malaysia -- Congresses; Education -- Malaysia -- Congresses